Pengaruh Metode Ekstraksi Dan Konsentrasi Etanol Terhadap Aktivitas Antibakteri Ekstrak Daun Sirih (Piper betle L) Pada Cutibacterium acnes - Vina Juliana Anggraeni; Lia Marliani; Dian Sri Herina (JURNAL FARMASI GALENIKA, 2026)
Piper betle L. leaves are known to contain various secondary metabolites with antibacterial potential; however, information regarding the effect of extraction methods and ethanol concentration on antibacterial activity against Cutibacterium acnes remains limited. This study aimed to evaluate the effect of extraction methods and ethanol concentration on the antibacterial activity of Piper betle leaf extract against C. acnes. Extraction was performed using maceration and reflux methods with 70% and 96% ethanol as solvents. Characterization was carried out through quality parameter evaluation, phytochemical screening, thin-layer chromatography (TLC), and bioautography analysis. Antibacterial activity was determined using the disc diffusion method at extract concentrations of 10%, 20%, and 30%. The results showed that maceration using 96% ethanol produced the highest yield (10.27%) and the strongest antibacterial activity with an inhibition zone diameter of 17.9 ± 0.42 mm at 30% concentration. Phytochemical screening confirmed the presence of flavonoids, tannins, saponins, alkaloids, and steroids/triterpenoids. Bioautography analysis revealed active spots that were presumed to contribute to antibacterial activity. Statistical analysis indicated that extract concentration and ethanol concentration significantly affected antibacterial activity (p < 0.05), whereas extraction methods did not show a significant effect. These findings indicate that Piper betle leaf extract has potential to be further developed as a natural source for anti-acne formulations.